Gestión administrativa y calidad de servicio en la Municipalidad Provincial de Loreto Nauta, 2023 - Mello Perez, Denis Orlando (2024)
The study aimed to specify the relationship between administrative management and service quality at the Municipalidad Distrital de Loreto Nauta in the year 2023. This research is descriptive-correlational, following a quantitative approach, a non-experimental design, and a cross-sectional approach. Two questionnaires were administered to 30 frequent employees of the organization. The existence of a strong optimal relational connection between the studied variables was discovered (r=0.986; p<0.005). It was concluded that there is a significant relational existence between administrative management and service quality at the Municipalidad Distrital de Loreto Nauta.